Influence of Co Content on Cracking Behavior and Wear Resistance of WCp-Reinforced FeCrMnCox HEAs Fabricated by the Laser Cladding Method - Wu, Wenxing; Qiu, Changjun; Zhou, Yinghao; Yan, Ming; Zhang, Yun; Li, Ruiqing; Chen, Pinghu (Frontiers in Materials, 2022)
High-entropy alloys (HEAs) have excellent properties of high strength-ductility, thermal stability, corrosion resistance, etc. HEAs can be considered as one of the most interesting structural or functional candidate materials, and have been extensively studied based on different multiple elements in the past decades. However, the previous works focus mainly on overcoming strength-ductility trade-off. In this paper, A series of WCp reinforced FeCrMnCox (x values in atomic ratio, x=0, 2, 4, 6, 8 and 10 at.%) HEAs is fabricated to investigate the influence of Co on the microstructures, microhardness, cracking behavior and wear resistance. The results indicate that γ phase (fcc structure) can be formed in the designed HEA with a small amount of α phase (bcc structure). Stress can result in cracking initiation owing to the formation of lattice distortion caused by the decomposition and diffusion of WC into the matrix, and cracking phenomenon is more serious when Co content is decreased gradually. In addition, microhardness is also increased gradually with decreasing Co content, and the maximum microhardness reaches 680 HV for the 0-2 sample without Co. Furthermore, excellent wear resistance of the designed materials can be attributed mainly to hardness rather than friction coefficient. A conspicuous monotonic decrease in wear rate is discovered with a monotonic increasing microhardness, adhesive wear mechanism appears mainly in the samples with higher Co content and wear mechanism is transformed gradually from typical adhesive wear mechanism to abrasive wear mechanism with the reduction of Co content.